Disparities in the Use of Necessary Defense (Noodweer) Versus Excessive Use of Necessary Defense (Noodweer Excess) Under Law No. 1 of 2023 - M.S. Alfarisi; Rona Indara; Yossie Irena; Soni Sunanta; Dini Santia (Journal of Social Research, 2026)
This research aims to analyze the regulation and position of the concepts of forced defense (noodweer) and excessive forced defense (noodweer excess) in Law Number 1 of 2023 concerning the Criminal Code, as well as their implications for the criminal accountability system in Indonesia. The research method used is normative juridical, employing statutory and conceptual approaches through the analysis of legal norms, doctrines, and related literature. The results of the study show that noodweer is regulated as a justification that removes the unlawful nature of an act, as reflected in provisions concerning defense against attacks or threats of attacks that are immediate and unlawful. Meanwhile, noodweer excessqualifies as an excuse that removes criminal liability, even though the act is still considered unlawful, due to severe mental shock caused by the attack. The fundamental difference between the two lies in the principle of proportionality in noodweer and psychological factors in noodweer excess. However, in law enforcement practice, there are still unclear parameters, especially regarding the limits of proportionality and the proof of mental shock. This study concludes that more comprehensive normative affirmation and interpretive guidelines are needed to provide legal certainty and prevent disparities in decisions in the application of the two concepts. In addition, the evidentiary mechanism distinguishing between justifying and excusing grounds needs to be formulated more systematically within the criminal justice system.